A randomized crossover clinical study showing that methylphenidate-SODAS improves attention-deficit/hyperactivity disorder symptoms in adolescents with substance use disorder - Szobot,C.M. (2008)
Our objective was to evaluate the effectiveness of a long-acting formulation of methylphenidate (MPH-SODAS) on attention-deficit/hyperactivity disorder (ADHD) symptoms in an outpatient sample of adolescents with ADHD and substance use disorders (SUD). Secondary goals were to evaluate the tolerability and impact on drug use of MPH-SODAS. This was a 6-week, single-blind, placebo-controlled crossover study assessing efficacy of escalated doses of MPH-SODAS on ADHD symptoms in 16 adolescents with ADHD/SUD. Participants were randomly allocated to either group A (weeks 1-3 on MPH-SODAS, weeks 4-6 on placebo) or group B (reverse order). The primary outcome measures were the Swanson, Nolan and Pelham Scale, version IV (SNAP-IV) and the Clinical Global Impression Scale (CGI). We also evaluated the adverse effects of MPH-SODAS using the Barkley Side Effect Rating Scale and subject reports of drug use during the study. The sample consisted of marijuana (N = 16; 100%) and cocaine users (N = 7; 43.8%). Subjects had a significantly greater reduction in SNAP-IV and CGI scores (P < 0.001 for all analyses) during MPH-SODAS treatment compared to placebo. No significant effects for period or sequence were found in analyses with the SNAP-IV and CGI scales. There was no significant effect on drug use. MPH-SODAS was well tolerated but was associated with more severe appetite reduction than placebo (P < 0.001). MPH-SODAS was more effective than placebo in reducing ADHD symptoms in a non-abstinent outpatient sample of adolescents with comorbid SUD. Randomized clinical trials, with larger samples and SUD intervention, are recommended.